Limited Rationality in the Use of Credit Cards in Ecuador - Villagómez-Cevallos, Byron (2018)
Economic theory is based on the existence of the so-called "representative agent" that makes rational decisions. However, it has been possible to demonstrate that many of the economic decisions made by consumers are based on the so-called "impulse", which makes them liable to fall into deception and manipulation, and in this sense the aforementioned rationality of the agent representative, paradigm of neoclassical theory, loses its validity and is overcome by cognitive economy.  The methodology used in this investigation is first of all bibliographic and then explanatory, based on several empirical tests carried out in several study groups.  The results obtained were decisive and are consistent with studies carried out in other countries (Akerlof, G., Shiller, R., 2015), that is, that consumers who use credit cards are willing to pay more for goods and services who acquire that those who pay in cash, that the beneficiaries of "cash advances" do not know the financial conditions of these consumer loans and that the delinquent debtors of the consumer portfolio through the so-called advances of cash with credit cards are harassed and intimidated by financial institutions.